How social integration affects the income of relocated households: evidence from China - Chuangxin Zhao; Manping Tang; Changxiang Wang (Frontiers in Sustainable Food Systems)
Ensuring the income of relocated households is of great theoretical and practical significance for improving their livelihoods and sustainable development. This article is based on micro survey data of relocated farmers in Sichuan Province, China, and analyzes the impact of social integration on the income level and structure of relocated farmers from both theoretical and empirical perspectives. The results show that: social integration has a significant positive effect on the household income level of relocated farmers, and the effect of social integration on household income decreases with the increase of income level. From the perspective of income structure, social integration improves the operating income, wage income and property income of relocated households, but the impact of social integration on transfer income is not obvious. Non-agricultural employment ability, information acquisition and life satisfaction are the mechanisms through which social integration affects household income. There are differences in the effect of social integration on household income among different groups of relocated farmers. Finally, according to the conclusion, the paper puts forward relevant countermeasures and suggestions to improve the level of social integration, improve the non-agricultural employment ability of relocated farmers, improve the quality of information acquisition and life satisfaction, and provide differentiated support for different groups.